Search for Senna Ever World - Applegate, Katherine (New York : Scholastic, Inc., 1999)
David's life was pretty normal. School. Friends. Girlfriend. Actually, Senna was probably the oddest aspect of his life. She was beautiful. Smart. But there was something very different about her. Something strange.
620
Accelerated Reader AR